2020
DOI: 10.5194/tc-14-1829-2020
|View full text |Cite
|
Sign up to set email alerts
|

The RHOSSA campaign: multi-resolution monitoring of the seasonal evolution of the structure and mechanical stability of an alpine snowpack

Abstract: Abstract. The necessity of characterizing snow through objective, physically motivated parameters has led to new model formulations and new measurement techniques. Consequently, essential structural parameters such as density and specific surface area (for basic characterization) or mechanical parameters such as the critical crack length (for avalanche stability characterization) gradually replace the semiempirical indices acquired from traditional stratigraphy. These advances come along with new demands and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 64 publications
0
50
0
Order By: Relevance
“…We evaluated the model performance by comparing simulated and measured snow depth, snow density and SSA ( Vertical profiles of snow density and SSA were retrieved from a SnowMicroPen (SMP), a snow penetrometer measuring the bonding force between snow grains with a vertical resolution of 1.25 mm (Schneebeli et al, 1999). While the density retrieved from SMP measurements was calculated following Calonne et al (2020), Proksch et al (2015) and King et al (2020), SSA was obtained based on Calonne et al (2020) and Proksch et al (2015), as King et al (2020) In addition, on 03 April 2018, snow depth was measured with a ruler, and every 10 cm of the profile, snow density with a density cutter (60x30x56 mm) and SSA with an IceCube3. The optical system IceCube measures the hemispherical infrared reflectance of snow and converts the reflectance in SSA (Zuanon, 2013).…”
Section: Validation Datamentioning
confidence: 99%
See 3 more Smart Citations
“…We evaluated the model performance by comparing simulated and measured snow depth, snow density and SSA ( Vertical profiles of snow density and SSA were retrieved from a SnowMicroPen (SMP), a snow penetrometer measuring the bonding force between snow grains with a vertical resolution of 1.25 mm (Schneebeli et al, 1999). While the density retrieved from SMP measurements was calculated following Calonne et al (2020), Proksch et al (2015) and King et al (2020), SSA was obtained based on Calonne et al (2020) and Proksch et al (2015), as King et al (2020) In addition, on 03 April 2018, snow depth was measured with a ruler, and every 10 cm of the profile, snow density with a density cutter (60x30x56 mm) and SSA with an IceCube3. The optical system IceCube measures the hemispherical infrared reflectance of snow and converts the reflectance in SSA (Zuanon, 2013).…”
Section: Validation Datamentioning
confidence: 99%
“…Proksch et al (2015) used data from the European Alps and the Arctic, while measurements for the parametrisation after Calonne et al (2020) were from the Swiss Alps and therefore for warm snow. However, Calonne et al (2020) developed the parametrisation for the SMP Version 4 we used, while the parametrisation after Proksch et al (2015) was developed for SMP Version 2 (Calonne et al, 2020). King et al (2020) found large discrepancies between measured density with a density cutter and SMP after Proksch et al (2015) for snow on Arctic sea ice.…”
Section: Snow Density and Ssa Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Three water transport schemes implemented in SNOW-PACK were evaluated. First, the bucket approach (BA) is a common method used in snow-cover models (e.g., Bartelt and Lehning, 2002;Vionnet et al, 2012), which assumes that water is transported to the next downward layer when the liquid water content exceeds the water holding capacity of a given layer (depending on the ice volumetric content of snow; Coléou and Lesaffre, 1998). Second, the Richards equation (RE) was implemented in SNOWPACK by Wever et al (2014) to account for capillary effects.…”
Section: Snowpack Simulations 221 Simulation Configurationmentioning
confidence: 99%